The investigation of the hotels service quality effects on tourist on tourist loyalty - Keshavarz, Yousef; Ali, Mass Hareeza (Marcial Pons Librero, 2015)
The present study aims to explore the relationship between service quality with tourist satisfaction and loyalty in the Malaysian hotel industry. In this research, the population was international tourists who stayin4 and 5-star hotels located in Kuala Lumpur, sample was selected based on clustering sample method. From the result, it was found that price had a significant effect on tourists` expectation toward hotels. Moreover, tourists` expectation has significant influence on perceived service quality but did not influence on their satisfaction. Finally, the result of this survey support that, tourist`s satisfaction and perceived service quality had significant influence on tourists` loyalty toward hotels. The result of this research is helpful for hotelier to plan new strategies for attracting more tourists therefore it leads to economic development in Malaysia.